Autoimmune bullous diseases during COVID-19 pandemic: 2022 update on rituximab and vaccine - Pira, Anna; Sinagra, Jo Linda Maria; Moro, Francesco; Mariotti, Feliciana; Di Zenzo, Giovanni (Frontiers in Medicine, 2023)
Autoimmune bullous diseases (AIBDs) are a heterogeneous group of life-threatening disorders associated with subepidermal or intraepidermal blistering. Skin barrier alterations and prolonged immunosuppressive treatments increase the risk of infections in patients with AIBDs, who are considered fragile. COVID-19 pandemic had a heavy impact on these patients. Although advances have been made in terms of prevention and treatment of COVID-19, this topic remains significant as the pandemic and its waves could last several years and, so far, a relevant proportion of the population worldwide is not vaccinated. This review is a 2022 update that summarizes and discusses the pandemic’s burden on AIBD patients mainly considering relevant studies in terms of: (i) sample dimension; (ii) quality of control populations; (iii) possible standardization by age, gender and country. The findings show that: (i) the risk of COVID-19 infection and its severe course were comparable in AIBD patients and in the general population, except for rituximab-treated patients that presented a higher risk of infection and severe disease; (ii) the mortality rate in COVID-19-infected bullous pemphigoid patients was higher than in the general population, (iii) 121 cases of AIBD onset and 185 cases of relapse or exacerbation occurred after COVID-19 vaccination and a causal relationship has not been demonstrated so far. Altogether, acquired knowledge on COVID-19 pandemic could also be important in possible, albeit undesirable, future pandemic scenarios.